THE INFLUENCE OF FERMENTATION DURATION ON THE NUTRITION CONTENT OF AVICENNIA MARINA LEAF FLOUR FERMENTED WITH RHIZOPUS ORYZAE - Safitri, Puput; Kusumawardani, Emi (LPPM STIKES HUSADA JOMBANG, 2026)
Abstract Background Avicennia marina has the highest protein content among mangrove plant species. Given its potential nutritional value, further research is required to maximise its utilisation. Processing Avicennia marina leaves into flour is one approach to improve usability and extend shelf life, as flour is more stable than fresh leaves. Fermentation can improve the nutritional value of Avicennia marina leaf flour, and one key factor influencing fermentation outcomes is fermentation duration. To date, no studies have examined how different fermentation durations affect the nutritional value of Avicennia marina leaf flour fermented with Rhizopus oryzae. Therefore, this study investigated the effect of fermentation duration on the nutritional value of Avicennia marina leaf flour fermented with Rhizopus oryzae. Objectives: This study aimed to determine the effect of fermentation duration on the nutritional value of Avicennia marina leaf flour fermented with Rhizopus oryzae. An experimental approach was employed to examine the cause–and–effect relationship between the independent and dependent variables. The study used a simple Completely Randomised Design (CRD) and an Honest Significant Difference (HSD) test (Tukey’s test) at the 5% significance level, using SPSS version 16. Methods: This study employed a simple completely randomised design (CRD) with five treatments and three replicates per treatment. The completely randomised design is the simplest of the available designs. No blocking was used; therefore, variation was attributed to treatment effects and experimental error. Results: The results showed that fermentation with R. oryzae was associated with higher nutrient composition in Avicennia marina leaf flour. After four days of fermentation, the highest protein content was 19.95%. After eight days of fermentation, the highest fat content was 7.21%, the highest ash content was 13.41%, and the highest crude fibre content was 16.78%. On the first day of fermentation, the highest moisture content was 11.43%, and the highest pH value was 5.70%. The fermented Avicennia marina leaf flour contained 4.28 g/100 g leucine and 12.60 g/100 g glutamic acid (a non-essential amino acid). Conclusion: Based on the findings of this study, further research is warranted to determine whether fermentation of Avicennia marina leaf flour with Rhizopus oryzae may be beneficial. Accordingly, additional studies are required to achieve more robust outcomes and to optimise the utilisation of fermented Avicennia marina leaf flour. Keywords: Avicennia marina leaf flour; Rhizopus oryzae; fermentation; amino acids